2020
DOI: 10.3390/ijms22010097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eltrombopag on In Vitro Macrophage Polarization in Pediatric Immune Thrombocytopenia

Abstract: Immune Thrombocytopenia (ITP) is an autoimmune disease characterized by autoantibodies-mediated platelet destruction, a prevalence of M1 pro-inflammatory macrophage phenotype and an elevated T helper 1 and T helper 2 lymphocytes (Th1/Th2) ratio, resulting in impairment of inflammatory profile and immune response. Macrophages are immune cells, present as pro-inflammatory classically activated macrophages (M1) or as anti-inflammatory alternatively activated macrophages (M2). They have a key role in ITP, acting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Eltrombopag license for chronic immune thrombocytopenia (ITP) treatment in both pediatric and adult patients when the rst-line therapy or splenectomy fail [20]. Eltrombopag improves T and B regulatory cells functions, suppresses T-cells activity, and inhibits monocytes activation in pediatric patients with immune thrombocytopenia (ITP) [21]. The combination of eltrombopag with an oral immunosuppressant and an androgen in patients with refractory severe aplastic anemia is feasible and could restore multi-lineage hematopoiesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Eltrombopag license for chronic immune thrombocytopenia (ITP) treatment in both pediatric and adult patients when the rst-line therapy or splenectomy fail [20]. Eltrombopag improves T and B regulatory cells functions, suppresses T-cells activity, and inhibits monocytes activation in pediatric patients with immune thrombocytopenia (ITP) [21]. The combination of eltrombopag with an oral immunosuppressant and an androgen in patients with refractory severe aplastic anemia is feasible and could restore multi-lineage hematopoiesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Also in ITP, it has been observed a prevalence of M1 macrophages, responsible for an increased release of pro-inflammatory cytokines [63,64]. Accordingly, the switch from the M1 pro-inflammatory phenotype to the M2 anti-inflammatory type in ITP pediatric patients is correlated to a reduction of the inflammatory state and to a restoration of the immune system function [65]. In accordance with these findings, Pereira et al demonstrated that acute iron deprivation in human macrophages causes anti-inflammatory responses.…”
Section: Iron and Inflammationmentioning
confidence: 99%
“…M1 macrophages are characterized by an elevated iron content which is responsible for inducing inflammation and inhibiting pathogen growth. They show anti-microbial, pro-inflammatory and anti-tumor properties, by releasing high levels of pro-inflammatory cytokines, such as IL-6, TNF-α, IL-1β and Nitric Oxide Synthase (iNOS) [65,132]. In contrast, M2 macrophages release high quantity of iron, thus contributing to cell proliferation.…”
Section: Metabolism and Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological effect of EPAG interactions with TPO-R results in an increase of differentiation and proliferation rate of the megakaryocytoblastic cellular line and its precursors. Alongside this effect on platelet count, recent evidence also suggests an immune-modulating and iron chelating property of EPAG ( Argenziano et al, 2021 ; Di Paola et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%